Pengaruh Penambahan Limbah Serbuk Besi dan Serbuk Kayu terhadap Kuat Tekan Beton - Putri, Sefti Maulana; Romadhon, Romadhon (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Concrete is a common material used to build buildings. The use of concrete materials is increasing, but the materials used to make concrete are increasingly expensive and limited. In this case it is necessary to innovate to save materials for making concrete by adding iron filings and sawdust, with the aim of knowing the effect of adding iron filings and sawdust to the compressive strength of concrete. In this study the ASTM method used was to analyze primary data. The data were obtained from research conducted in the laboratory using the analytical test method of cement, fine aggregate, coarse aggregate, and additives (iron filings and wood powder). Research results from 3 variations of class 1 iron powder and sawdust mixtures used with variations of 1% iron powder 1% wood powder, 2% iron powder 2% wood powder, and 3% iron powder 3%. The variation values that have high stability are the Normal variation (0% added material) and the 1% iron powder 1% wood powder variation with stability values of 14.82 MPa and 14.50 MPa. Variation levels of 1% iron filings and 1% sawdust are stated to be the most effective for mixing concrete because the compressive strength values of this variation already meet the SNI specifications, so the variations of iron filings and wood powder added materials are the most optimal to be used as K-175 concrete mix ingredients.